User‐friendly XOR‐based visual secret sharing by random grid. (1st September 2018) - Fan, Tzuo‐Yau; Chao, Her‐Chang
Abstract : This study proposes a user‐friendly XOR‐based visual secret sharing scheme using random grids. In some visual secret sharing schemes, problems such as pixel expansion or noisy and meaningless shares may be encountered. In the proposed scheme, different regions in the shared image will have different brightness levels depending on the cover image's pixel values so that the generated shares contain information regarding the cover image and are not just a meaningless noisy image. This can overcome the difficulty in recovering the secret image in cases wherein the shares were mixed up by mistake. Furthermore, the dimension of the share is the same as the secret image and there are no pixel expansion problems. The size of the recovered secret image is consistent with the size of the original secret image, and there are no changes in scaling. Lastly, although one of the generated share is a complementary cover image, the image quality of the recovered secret image is still favourable when the secret image is recovered. The experimental and analysis results demonstrate that the proposed scheme is more effective than other schemes.